Longitudinal Associations Between Vitamin D Metabolites and Sarcopenia in Older Australian men: The Concord Health and Aging in Men Project. (25th May 2017) - Hirani, Vasant; Cumming, Robert G; Naganathan, Vasi; Blyth, Fiona; Le Couteur, David G; Hsu, Benjumin; Handelsman, David J; Waite, Louise M; Seibel, Markus J
Abstract: Background: To explore the associations between serum 25-hydroxyvitamin D (25D) and 1, 25-dihydroxyvitamin D (1, 25D) levels at baseline and incidence of sarcopenia over time in older Australian community-dwelling older men. Methods: Of the 1, 705 men aged ≥70 years (2005–2007) participating in the Concord Health and Ageing in Men Project, those without sarcopenia at baseline ( n = 1, 312 for 25D and n = 1, 231 for 1, 25D), 2 years ( n = 1, 024 for 25D and n = 956 for 1, 25D), and 5-year follow-up ( n = 709 for 25D and n = 663 for 1, 25D) were included in the study. The main outcome measurement was the incidence of sarcopenia defined as appendicular lean mass adjusted for body mass index <0.789 and grip strength <26.0 kg. Serum 25D and 1, 25D levels were measured at baseline by radioimmunoassay (Diasorin, Stillwater, MN) and categorized into quartiles as predictor variables. Covariates included age, income, season of blood collection, physical activity, vitamin D supplement and medication use, measures of health, serum parathyroid hormone (PTH), estimated glomerular filtration rate (eGFR), albumin, and white blood cell count. Results: In this study, incidence of sarcopenia was 3.9% in men at the 2-year follow-up and 8.6% at the 5-year follow-up. In adjusted analysis, men with vitamin D levels in the lowest quartiles (25D <40nmol/L; 1, 25D <62 pmol/L) showed significant associations with increased odds of incident sarcopenia compared to those with vitamin D levels in the highest quartiles over 5 years. [25D: odds ratio (OR) 2.53 (95% confidence interval (CI) 1.14, 5.64) p = .02; 1, 25D: OR 2.67 (95% CI 1.28, 5.60) p = .01]. After further adjustments for the respective other serum vitamin D measure, (either 25D or 1, 25D), the association remained significant [25D: OR 2.40 (95% CI 1.02, 5.64) p = .04; 1, 25D: OR 2.23 (95% CI 1.04, 4.80) p = .04]. Conclusion: Low serum 1, 25D and 25D concentrations at baseline are independently associated with the incidence of sarcopenia over the subsequent 5 years. Although our data do not prove any causal relationship, it is conceivable that maintaining vitamin D sufficiency may reduce the incidence of sarcopenia in ageing men.